Impaired lung function following e‐cigarette or vaping product use associated lung injury in the first cohort of hospitalized adolescents. Issue 7 (22nd April 2020) - Carroll, Brian J.; Kim, Michael; Hemyari, Ali; Thakrar, Pooja; Kump, Theresa E.; Wade, Thomas; De Vela, Gabriel; Hall, Jaimee; Diaz, Christina D.; D'Andrea, Lynn A.
Abstract: Background: Beginning June 2019, Children's Wisconsin was the first hospital to identify a cohort of adolescent patients hospitalized with symptoms likely associated with e‐cigarette use. Our report adds to the growing literature describing the radiographic, gross and cytopathologic bronchoscopic findings, and short‐term lung function outcomes in this cohort of adolescents with e‐cigarette or vaping product use associated lung injury (EVALI). Methods: We present 15 adolescents hospitalized from June to September, 2019 with confirmed EVALI. We abstracted data from inpatient hospitalization and first outpatient pulmonary clinic visit. Results: There were 15 patients (11 male, 12 White) with a mean age of 17.1 years. All patients presented with subacute pulmonary, gastrointestinal and constitutional complaints. Diagnostic workup was guided by the Centers for Disease Control criteria for confirmed EVALI case surveillance. Flexible bronchoscopy was performed in 13/15 patients with 10/13 demonstrating gross pathologic abnormalities. Seven of 15 patients required intensive care and 2 met criteria for pediatric Acute Respiratory Distress Syndrome. Patients had dramatic improvement with systemic glucocorticoid therapy and 14/15 were discharged on room air. Eleven patients were seen as outpatients. Despite 11/11 patients reporting resolved or improved symptoms, 7/11 had abnormalities on pulmonary function testing. We initiated inhaled corticosteroids for 5/11 patients and 4/11 patients remained on their corticosteroid wean. Conclusions and Relevance: We report short‐term outcomes of the first cohort of adolescent patients hospitalized with EVALI. An association is observed between clinical improvement and treatment with systemic corticosteroids. However, residual airway reactivity or diffusion abnormalities persisted when patients were re‐evaluated in the short‐term period (mean 4.5 weeks).